GERARD GENETTES’ NARRATIVE STRUCTURE IN THE SHORT STORY 'KAYYU YANG TAK LAYU' BY YULI MAHARANI - Al Anshory, Abdul Muntaqim; Putri, Firsya Aulia; Salis, Rohmatulloh (Annual International Conferences on Language, Literature, and Media, 2023)
The analysis of narrative structure is the key to understanding the deeper layers of literary works. This research aims to determine the narrative structure contained in the short story Kayyu Yang Tak Layu by Yuli Maharani, which is a motivational short story in the antalogy of Wonderful Stories based on the perspective of Gerard Genette. Gerard Genette is a literary theorist who focuses his studies on narrative structure. In this case, Gerard Genette divides the narrative structure into five elements, namely order, duration, frequency, mood and voice. The research method used is a qualitative descriptive method. Where the results obtained from the analysis are, (1) Order, the narrative sequence, which is used in the short story Kayyu Yang Tak Layu is achrony. (2) Duration, the duration of the narrative, which is used is the scene and summary. (3) Frequency, narrative frequency, in this short story is in the form of singulative repetition. (4) Mood, narrative mode, in this short story the narrator is not a character in the story and the focalization technique used is zero focalization. (5) Voice, narrative voice, in the short story Kayyu Yang Tak Layu uses the time of storytelling in the form of simultaneous and the version used by the narrator is a heterodiegetic narrator, and the narrative level is in the form of extradiegetic-heterodiegetic.